Canine oral primary melanoma cells exhibit shift to mesenchymal phenotype and phagocytic behaviour. (29th May 2019) - Schmid, Franziska; Brodesser, Daniela; Reifinger, Martin; Forte, Sara; Semp, Pia; Eberspächer‐Schweda, Matthias C.; Wolschek, Markus; Brandt, Sabine; Kleiter, Miriam; Pratscher, Barbara
Abstract : Canine oral malignant melanoma (COMM) is a potentially lethal cancer disease. We established primary cell lines from mostly amelanotic primary COMM and metastases and assessed lesions and derived cells for Melan A, PNL2 and CD146 expression. Then, migration and invasion of CD146‐enriched vs ‐depleted COMM cells were analysed. Epithelial‐to‐mesenchymal transition (EMT) was addressed by Vimentin‐staining and MMP2/MMP9 zymography. Phagocytic behaviour was analysed by histopathological examination and phagocytosis assay. While Melan A‐ and PNL2‐staining yielded inconsistent data, 100% of COMM sections and primary cells showed CD146 expression, suggesting that this protein may serve as a prognostic marker. An overall correlation between CD146‐expression and migration/invasion was not observed. All primary cell lines consistently expressed Vimentin and secreted biologically active MMP2, indicating that they had undergone EMT. Importantly, COMM sections exhibited cell‐in‐cell structures, and all primary cell lines exhibited phagocytic activity, supporting the concept that cell cannibalism may have a role in COMM progression.